PWE-028 Thiopurine-induced neutropaenia in IBD patients with normal TPMT levels: a warning for gastroenterologists. (23rd September 2015) - Cherian, S; Saxena, V; Foxton, M; McNair, A
Abstract : Introduction: Myelotoxicity occurs in approximately 3% of patients receiving Azathioprine (AZA) or Mercaptopurine (MP). Manufacturers recommend weekly blood testing for the first 8 weeks of therapy but BSG guidelines state that "less frequent monitoring (within 4 weeks) may be sufficient". Some gastroenterologists elect to monitor patients with normal thiopurine methyl transferase (TPMT) levels less intensively, believing that neutropaenia is less frequently encountered in this group. We performed a retrospective review to determine the proportion of IBD patients on our unit with AZA/MP-induced neutropaenia who had low TPMT levels. Methods: We reviewed the medical records of our IBD patients who had become neutropenic on AZA/MP over the last 2 years. Patients received standard recommended doses: 2–2.5 mg/kg AZA, 1–1.5 mg/kg MP. TPMT had been measured prior to therapy in all patients. All patients had blood tests done at fixed intervals according to a local protocol to monitor myelotoxicity. Result: Over the last 2 years, 8 patients were identified, who had developed myelosupression on AZA/MP therapy. Five patients had Ulcerative colitis. Average age at start of AZA/MP was 51.8 years (range 31–74 years). Average disease duration prior to immunosuppression was 8.7 years (range 1–21 years). MP was used in 7 patients. Only one of the patients had a low TPMT level 24 (normal range 26–50 PM/h/mgH). Mean time to myelosupression was 4.7 weeks (range 2–7 weeks). Lowest recorded WCC ranged from 0.6–2.7×10 9 /L (median-1.8×10 9 /L) and neutrophils ranged from 0–1.4×10 9 /L (median 0.75×10 9 /L). Conclusion: The majority (7 of 8) of our patients with thiopurine-induced myelotoxicty had normal TPMT levels. Half of our patients developed neutropaenia within 4 weeks of treatment. The results of TPMT level should not influence the frequency of blood test monitoring in the first 8 weeks of therapy. The current BSG guidelines should be amended to emphasise the importance of frequent blood test monitoring. We advise caution when using thiopurine and suggest weekly FBC for the first 8 weeks, even if the TPMT is normal.